2014
DOI: 10.1038/nature12971
|View full text |Cite
|
Sign up to set email alerts
|

DNA-guided DNA interference by a prokaryotic Argonaute

Abstract: RNA interference is widely distributed in eukaryotes and has a variety of functions, including antiviral defence and gene regulation1,2. All RNA interference pathways use small single-stranded RNA (ssRNA) molecules that guide proteins of the Argonaute (Ago) family to complementary ssRNA targets: RNA-guided RNA interference1,2. The role of prokaryotic Ago variants has remained elusive, although bioinformatics analysis has suggested their involvement in host defence3. Here we demonstrate that Ago of the bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
552
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 388 publications
(604 citation statements)
references
References 32 publications
23
552
5
2
Order By: Relevance
“…S1D). However, attempts to purify native protein using immunoprecipitation were not successful, consistent with previous reports of low Ago concentrations in bacteria and archaea (6)(7)(8).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…S1D). However, attempts to purify native protein using immunoprecipitation were not successful, consistent with previous reports of low Ago concentrations in bacteria and archaea (6)(7)(8).…”
Section: Resultssupporting
confidence: 69%
“…Recent studies suggested that DNA-guided bacterial and archaeal Argonaute proteins are directly involved in host defense by cleaving foreign DNA elements, such as DNA viruses and plasmids (6,7). In addition, a catalytically inactive Argonaute protein in Rhodobacter sphaeroides (RsAgo) was demonstrated to use RNA guides and possibly recruits an associated nuclease for subsequent target cleavage (8).…”
mentioning
confidence: 99%
“…The molecular pathway that mediates DNAi in O. dioica will be the focus of future investigations. As a host defence against invading DNA, it has recently been reported that Argonaute protein of T. thermophilus (TtAgo) mediates small single-stranded DNA-induced DNAi [10]. Similarly to TtAgo, Argonaute of O. dioica may mediate DNAi, inhibiting transcription and degrading mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study of the archaean Thermus thermophilus has suggested that it may have a system for DNA-induced DNAi [10]. Argonaute protein in T. thermophilus has shown to cleave exogenously supplied DNA strands in a sequence-specific manner [10]. While RNAi is a highly conserved genesilencing system in a wide range of eukaryotes, DNAi has not been explored in any multicellular animals studied to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation